(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The French philosopher Francois Jacob believes that the proof of design for the living world has long been established and has for some time been the most important pillar of faith for man. However, the discipline and complexity of the world’s precision and for a certain period of time set the axiomatic mentality of the applied sciences that need no explanation. This discipline formed one of the greatest dilemmas before anyone who sees that the universe is a closed system of matter and energy has no extension from the outside and among those who see the existence of complexity and telemetry in each part of its parts. Despite the adoption of science and a long period of evolutionary thought and the adoption of its own concepts, including the concept of coincidence, which investigates the design of teleology, but modern biological research has pushed the design to become a scientific theory of integrated dimensions address the issue of the emergence of living organisms, because the nature of the objects and the parts that are formed and revealed by studies Molecularity and specifically the dazzling DNA that is responsible for all the characteristics of the organism needs its origin, its survival and its work to be intelligible. Randomity can not be explained by the fact that the creativity of intelligence for anything imposes the appearance of design marks on itWe have presented this research on one of the most prominent concepts incontemporary biology ..